2013
DOI: 10.1089/ten.tea.2012.0172
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cell-Derived Mesenchymal Stem Cell Seeding on Calcium Phosphate Cement-Chitosan-RGD Scaffold for Bone Repair

Abstract: Calcium phosphate cement (CPC) has in situ-setting ability and excellent osteoconductivity. Human embryonic stem cells (hESCs) are exciting for regenerative medicine due to their strong proliferative ability and multilineage differentiation capability. However, there has been no report on hESC seeding with CPC. The objectives of this study were to obtain hESC-derived mesenchymal stem cells (hESCd-MSCs), and to investigate hESCd-MSC proliferation and osteogenic differentiation on novel CPC with chitosan immobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 67 publications
8
94
0
1
Order By: Relevance
“…Figure 5 showed that cell metabolic rate increased in RGD-modified PAMAM (dendrimer 5) hydrogels in comparison to the control PAMAM (dendrimer 4) hydrogel without RGD. The explanation could be that the RGD peptide enhanced proliferation of BMSCs in the hydrogel culture, which was consistent with the reports by Kim et al [51] and Chen et al [52] This fibronectin-derived peptide sequence RGD is well known for its ability to promote cellular attachment by binding to integrin receptors. This interaction was also shown to play an important role in cell growth and overall regulation of cell functions.…”
Section: Journal Of Biomaterials Science Polymer Edition 679supporting
confidence: 88%
“…Figure 5 showed that cell metabolic rate increased in RGD-modified PAMAM (dendrimer 5) hydrogels in comparison to the control PAMAM (dendrimer 4) hydrogel without RGD. The explanation could be that the RGD peptide enhanced proliferation of BMSCs in the hydrogel culture, which was consistent with the reports by Kim et al [51] and Chen et al [52] This fibronectin-derived peptide sequence RGD is well known for its ability to promote cellular attachment by binding to integrin receptors. This interaction was also shown to play an important role in cell growth and overall regulation of cell functions.…”
Section: Journal Of Biomaterials Science Polymer Edition 679supporting
confidence: 88%
“…In recent years, the use of CTS as a bone cement additive became very popular [24,25]. Chitosan is a cationic natural copolymer of glucosamine and biodegradable mucoadhesive polysaccharide derived from the total or partial deacetylation of chitin.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 However, the application of hESCs in bone regenerative medicine requires the development of efficient methodologies for differentiating hESCs into an osteogenically committed lineage in vitro and production of functional bone formation in vivo. Osteogenic commitment and stem cell-based bone tissue engineering may be augmented through systemic administration of growth/bioactive factors or by scaffold-mediated delivery of these factors.…”
Section: Discussionmentioning
confidence: 99%